Communication electronics : RF design with practical applications using Pathwave/ADS software - Long, Stephen I. (River Publishers series in communications and networking., 2023)
This text/reference develops practical intuition into the art of RF circuit design and introduces users to the widely used simulation tool, Pathwave ADS, from Keysight Technologies. By using project-oriented assignments, it builds a strong foundation and focuses on practical applications illustrated by examples, simulation tutorials, and homework problems. Learning through doing has proven to be an effective preparatory tool for more advanced and complex applications, and this book is developed from the author⁰́₉s lecture notes for a senior/graduate class at University of California Santa Barbara. The class had a significant lab component employing measurement techniques, board-level prototyping, and RFIC design. Falling somewhere between a traditional textbook and a practical handbook, it focuses mainly on analog RF analysis and design and circuit simulation techniques.